Imperial Muslims Islam, Community and Authority in the Indian Ocean, 1839-1937 - Reese, Scott S. (Edinburgh University Press, 2017)
A great deal has been written about the webs, nodes and networks created by Britain's Indian Ocean Empire during the nineteenth and twentieth centuries. Much of the focus has been on the political, legal or economic consequences of empire; this book redresses the balance, devoting its attention to the personal and social. Using the British Settlement of Aden, it examines the development of a local Muslim community within the spaces created by imperial rule from the mid-nineteenth through mid-twentieth century. It explores how individuals from widely disparate backgrounds brought together by the networks of empire created a cohesive community utilizing the one commonality at their disposal: their faith. Specifically, it examines how religious institutions and spiritual ideas served as parameters for the creation of community and the kinds of symbolic and cultural capital an individual needed to attain communal membership and influence within the confines of imperial rule.